Raphaneae, Syrien - Gschwind, Markus (e-Forschungsberichte des DAI, 2023)
The fieldwork carried out in the legionary fortress of Raphaneae in western Syria provides valuable information on the Roman military presence in the frontier zones in Parthian and Sasanian Persia. Moreover, it allows a detailed insight into the changing attitudes and organization of Roman power in this important area. Currently, the data of the field project is processed for the preparation of the final publication.